Rehabilitation in the New Machine? Exploring Drug and Alcohol Use and Variables Related to Success among DUI Offenders Under Electronic Monitoring - Some Preliminary Outcome Results - Courtright, Kevin E. (International journal of offender therapy and comparative criminology, 2000)
When the "Western County" Penn. Probation Department implemented a house arrest with electronic monitoring EM program in the fall of 1992, offenders convicted under the commonwealth's mandatory driving under the influence DUI act were divided into two groups: One group went to jail and the other group served their sentence under house arrest with EM. Using descriptive and inferential statistics, this article examines differences in drug and alcohol consumption between the two groups and variables related to success for those in the EM program. With regard to drug and alcohol consumption, although differences did exist, they were not significant. However, using cross-tabulation tables and chi-squares, it was determined that two variables - successful attendance at treatment and employment - were significantly related to success while on EM. Such findings indicate the importance of both variables in the selection and supervision process